Identification, Characterization, and Expression Analysis Reveal Diverse Regulated Roles of Three MAPK Genes in Chlamys farreri Under Heat Stress - Liu, Zhi; Huang, Xiaoting; Yang, Zujing; Peng, Cheng; Yu, Haitao; Cui, Chang; Hu, Yuqing; Wang, Xuefeng; Xing, Qiang; Hu, Jingjie; Bao, Zhenmin (Frontiers in Physiology, 2021)
Mitogen-activated protein kinase (MAPK) cascades are fundamental signal transduction modules in all eukaryotic organisms, participating growth and development, as well as stress response. In present study, three MAPK genes were successfully identified from the genome of Chlamys farreri, respectively named CfERK1/2, CfJNK and Cfp38, and only one copy of ERK, JNK and p38 were detected. Domain analysis indicated that CfMAPKs possessed the typical domains, including S_TKc, Pkinase and PKc_like domain. Phylogenetic analysis showed that three CfMAPKs of MAPK subfamilies exists in the common ancestor of vertebrates and invertebrates. All CfMAPKs specifically expressed during larval development and in adult tissues, and the expression level of CfERK1/2 and Cfp38 was apparently higher than CfJNK. Under heat stress, the expression of CfERK1/2 and Cfp38 significantly down-regulated and then up-regulated in four tissues, while the expression of CfJNK increased in all tissues, these different expression patterns suggested a different molecular mechanism of CfMAPKs for bivalve to adapt to temperature changes. The diversity of CfMAPKs and their specific expression patterns provide valuable information for better understanding the functions of MAPK cascades in Bivalve.